Sunday

December 21, 2014

December 21, 2014

Posted by **Anonymous** on Tuesday, August 26, 2014 at 12:19am.

- math -
**Bosnian**, Tuesday, August 26, 2014 at 1:55am(6x^4-x^3+11x^2-2x-2)/(3x+1) =

2x^3-x^2+4x-2

Go on :

c a l c 1 0 1 . c o m

When page be open click option :

long division

When page be open in rectangle :

Divide

type :

6x^4-x^3+11x^2-2x-2

In rectangle :

by

type : 3x +1

Then click option :

DO IT

**Answer this Question**

**Related Questions**

math - I solved this problem 12x-6=11x -6+6=0 11x+6 12x=11x+6 12x-11x=x 11x-11x=...

Math - Can anyone help work these problumns out step by step? 11x-37=x+23 10p-26...

math polynomials - Simplify 4q^2-5q-1+8q^2+8q-9 A. -4q^2+3q+8 B. 12q^2+3q-10 C...

Math - Simplify 3(x - 4) + 8(x + 2). A)11x - 4 B)11x + 4 C)11x - 2

math - what is the equation of a line that passes through (1,-4) and (2,7)? a. y...

MATH - Algebra - 11x^2 + 22x/11 Am I on the right track? 11(x^2 + 11x)/11 = x^2...

Algebra 1b! - 1. Find the excluded value of x for the polynomomial expression ...

Algebra - Add the following (-8^2-2x+4)+(x^2-9x+7) A)9x^2-7x+11 B)-8x^2+11x+11 C...

math - The equation that has the roots 1, 2, 3 is: (a) x3 + 6x2 – 11x + 6 (b) x3...

math please help me - 6x + 4(2x + 3) = 34 + 3x 6x + 4(2x) + (4)(3) = 34 + 3x 6x...